Investigation into the Enhancement Effects of Combined Bioremediation of Petroleum-Contaminated Soil Utilizing Immobilized Microbial Consortium and Sudan Grass - Tie-Jun Wang; Zi-Yue Ding; Zi-Wei Hua; Zi-Wang Yuan; Qiu-Hong Niu; Hao Zhang (Toxics)
Petroleum-contaminated soil is an increasingly severe environmental issue. The integration of phytoremediation and microbial remediation can effectively mitigate their individual limitations and enhance remediation efficiency. In this study, four newly isolated bacterial strains (including Cytobacillus and Rhodococcus) that exhibited preferential degradation of distinct petroleum components were combined with the rhamnolipid-producing strain Pseudomonas aeruginosa SL-1. The immobilization of this petroleum-degrading microbial consortium was performed by biochar adsorption and sodium alginate embedding, subsequently optimized using response surface methodology (0.75 g·L−1 of biochar, 40 g·L−1 of sodium alginate, and 40 g·L−1 of calcium chloride). The results showed that the highest petroleum degradation rate (97.1%) of immobilized bacterial consortium was achieved at 72 h at a petroleum concentration of 5.0 g·L−1. When combined with Sudan grass for soil bioremediation, the degradation rate reached 72.8% after 120 d for soil containing 5.0 g·kg−1 of petroleum, higher than the results for the treatments with only immobilized bacterial consortium (53.0%) or Sudan grass (49.2%). Furthermore, significant improvements were observed for soil pH; nitrogen, phosphorus, and potassium contents; and urease, dehydrogenase, and catalase activities. Composite treatment also significantly increased the diversity and richness of the soil bacterial community and regulated its structure, function, and network composition. This study offers theoretical insights and potential practical applications for the enhanced bioremediation of petroleum-contaminated soils.